Kino w czasach pandemii: werbalne reprezentacje wątku epidemii w wielojęzycznych przekładach tytułów filmowych - Mocarz-Kleindienst, Maria (Acta Neophilologica, 2022)
The main purpose of this study was to research the extent to which viewers could recognize epidemic-themed movies based on the semantic and affective signals contained in the translated movie titles. The analysis revealed that viewers would find information about the epidemic in each of the examined language versions (i.e. German, Polish, and Russian) to at least the same extent as they did in the original version (usually English). The task of German-speaking viewers is the easiest one as the majority of translated titles contain clear semantic signals. Polish and Russian viewers receive slightly fewer such signals. All three language versions contain a similar number of affective signals adequate to the film genres: disaster film, science fiction, and thriller.